The Advances and Biomedical Applications of Imageable Nanomaterials - Xiang, Xiaohong; Shi, Doudou; Gao, Jianbo (Frontiers in Bioengineering and Biotechnology, 2022)
Nanomedicine shows great potential in screening, diagnosing and treating diseases. However, given the limitations of current technology, detection of some smaller lesions and drugs’ dynamic monitoring still need to be improved. With the advancement of nanotechnology, researchers have produced various nanomaterials with imaging capabilities which have shown great potential in biomedical research. Here, we summarized the researches based on the characteristics of imageable nanomaterials, highlighted the advantages and biomedical applications of imageable nanomaterials in the diagnosis and treatment of diseases, and discussed current challenges and prospects.